PENGARUH MOTIVASI DAN PENGEMBANGAN DIRI TERHADAP PRESTASI KERJA DOSEN - bahrudi efendi damanik (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
The purpose of this study is to determine the effect of motivation on the work performance of lecturers, to determine the influence of self-development of lecturer work performance, and to know simultaneously the influence of motivation and self-development of the lecturer's work performance. The result of this research is the variable of motivation and self development together have positive and significant influence to the work performance of lecturer can be shown with the value of F> F table (39 387> 3.320), the variable of self development partially have positive and significant effect to the performance of lecturer, with t count> t table (6,409> 1697), the variable of motivation partially positive and significant effect on the work performance of lecturer with t arithmetic> t table (6953> 1697), R Square value in the above table is 0.738, it shows that 73,80% variable of work achievement of lecturer can be explained by the variable of motivation and self development, while the rest 26,20% is explained by other factors not examined.